Evaluating the Results of CD31 and CD34 Expression on Skin Vessel Endothelial Cells After Radiotherapy by Stereological Method - Tuong, Vuong; Hoang Thanh, Tuan (Image Analysis and Stereology, 2025)
Skin damage is one of the most frequent side effects during radiotherapy in patients with cancer diseases. In this study, the stereological method was used to assess the level of CD31 and CD34 expression on the skin microvascular endothelial cells after radiotherapy. We collected thirty radiation-ulcer skin samples, each of which has three studied regions: area of ulcer, adjacent area and unwounded area. We found that the surface density (Sv) and length density (Lv) of blood vessel with CD31 and CD34 positive decreased significantly from center to outside of the ulcer. We conclude that stereological method could be used to evaluate the results of CD31 and CD34 expression on skin microvascular endothelial cells after radiother-apy. Moreover, the success of our study may permit to following application of this morphological quanti-tative method for analysis of further immunohistochemistry studies.